Purification of fuel grade Dimethyl Ether in a ready-to-assemble plant - Ballinger, Sarah (My University, 2016)
Due to the remote and dispersed nature of Alberta’s oil wells, it is not economical for the energy industry to capture all of the solution gas produced and as a result, the gas is being flared and vented in significant amounts. The objective of this research is to aid in the conversion of solution gas into dimethyl ether (DME) in a remote location by designing a distillation column that purifies DME and its reaction by-products, carbon dioxide, methanol and water. In order to develop an implementable solution, the distillation equipment must fit inside of a 40-foot shipping container to be transported to remote locations. Given the size constraint of the system, process intensification is the best strategy to efficiently separate the mixture. Several process intensification distillation techniques are explored, including semicontinuous distillation, the dividing wall column (DWC) and a novel semicontinuous dividing wall column (S-DWC). The traditional semicontinuous distillation column purifies DME to fuel grade purity, however the other components are not separated to a high enough grade given the height constrain of the system. The DWC and S-DWC both purify DME to its desired purity along with producing high purity waste streams. The S-DWC purifies the reaction intermediate methanol to a grade slightly higher than the DWC and is pure enough to recycle back to the reactor. An economic comparison is made between the three systems. While the DWC is a cheaper method of producing DME, the trade-off is the purity of the methanol produced. Overall, this research shows that it is possible to purify DME and its reaction by-products in a 40-foot distillation column at a cost that is competitive with Diesel.
Keywords: dimethyl ether, process intensification, dividing wall column, semicontinuous distillation, Aspen Plus Dynamics, computer simulation